ANALYSIS CORPORATE SUSTAINABILITY PRACTICE AT THE OIL COMPANY IN SOUTH KALIMANTAN - Budi Rofelawaty; Asfida Parama Rani (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, Industrial world have major contribution earth or environmental damage around the company. For that the company should make a pattern work focuses on the preservation of the environmental where he is, push the level of damage the environmental, and responsible of the welfare and health of the community around the company. If the company not take that responsible, it will impact to the reputation and value of the firm, and finally will impact to the sustainability of the company. Solutions that can be offered is to work patterns and the application of sustainable corporate strategies, attention to ethics in business by working patterns and strategy of the company’s work or the implementation of sustainable management like the implementation of Corporate Social Responsibility (CSR) program. This research explores accountability for corporate sustainability practice at the oil company in the context of governmental company in South Kalimantan. The analysis was through the implementation of Corporate Social Responsibility program for the community at Tanjung, one of local area in South Kalimantan. This study is quality research with 54 respondents as sample in 6 villages at ring one around of The exploration and production area of The Oil Company and 3 assistant manager of that company. The result showed that the implementation of CSR program is not work yet. CSR program are not run according to the main objectives of CSR program namely economic development, welfare and public health around the company. The implementation of CSR program just evidence that the company has met or liability regulations implementing CSR. CSR program are not implemented properly, because the program is grand strategy that determined by the central office Jakarta, before implemented that’s program without adjustment process and assessment with local values.